Mechanical Properties of Glass Ionomer Cements after Incorporation of Marine Derived Hydroxyapatite - Bilić-Prcić, Maja (Materials (Basel), 2020)
The purpose of this study was to evaluate the effects of the incorporation of hydroxyapatite (HA) derived from cuttlefish bone on the mechanical properties of glass ionomer cements (GIC). Fuji II LC and Fuji IX GP Extra (GC Corporation, Tokyo, Japan) were used in the study. There were four groups (n = 11–18) for each material: a group without the addition of HA particles and three groups modified by incorporation of 2, 5, and 10 wt% HA. The tests were performed on a universal testing machine (Shimadzu, Duisburg, Germany) and descriptive statistics, two-way analysis of variance (ANOVA) for the comparison of three mechanical properties, and one-way ANOVA for the comparison of different concentrations for each material were performed. Regarding the Fuji IX groups, compressive strength (CS) and flexural strength (FS) were highest in the group without HA particles added. The differences in CS between the Fuji IX group without HA particles and the Fuji IX groups with 2 wt% HA and 10 wt% HA were significant. The Fuji II 5 wt% HA group exhibited higher diametral tensile strength (DTS) and CS than other Fuji II groups, but not significantly. The Fuji II group, modified with 10 wt% HA, exhibited significantly higher FS than the Fuji II group without HA particles (p < 0.05). Porous HA incorporated into the Fuji IX groups had a significant impact on mechanical properties only in the Fuji IX 5 wt% HA group. Fuji II groups modified with 10 wt% HA showed the most favorable results with respect to FS.